2014
DOI: 10.1017/s0305000914000439
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic-phonetic differences between infant- and adult-directed speech: the role of stress and utterance position

Abstract: Previous studies have shown that infant-directed speech (IDS) differs from adult-directed speech (ADS) on a variety of dimensions. The aim of the current study was to investigate whether acoustic differences between IDS and ADS in English are modulated by prosodic structure. We compared vowels across the two registers (IDS, ADS) in both stressed and unstressed syllables, and in both utterance-medial and -final positions. Vowels in target bisyllabic trochees in the speech of twenty mothers of 4- and 11-month-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 34 publications
4
26
1
Order By: Relevance
“…Second, whole content words would be more strongly prominent at the phrasal level, through higher F0, greater duration, and, as seen in DePaolis et al 2010, longer pauses, which would facilitate their extraction. Third, lexically stressed syllables would have higher pitch in IDS over ADS, less so unstressed syllables (Wang, Seidl, & Cristia, 2015), enhancing the contrast between stressed and unstressed syllables and therefore aiding metrical segmentation (see also evidence for greater durational differences between stressed and unstressed syllables in IDS: Albin & Echols, 1996). Finally, more repetition and higher frequency of pausing should also serve to boost word learning.…”
Section: Discussionmentioning
confidence: 99%
“…Second, whole content words would be more strongly prominent at the phrasal level, through higher F0, greater duration, and, as seen in DePaolis et al 2010, longer pauses, which would facilitate their extraction. Third, lexically stressed syllables would have higher pitch in IDS over ADS, less so unstressed syllables (Wang, Seidl, & Cristia, 2015), enhancing the contrast between stressed and unstressed syllables and therefore aiding metrical segmentation (see also evidence for greater durational differences between stressed and unstressed syllables in IDS: Albin & Echols, 1996). Finally, more repetition and higher frequency of pausing should also serve to boost word learning.…”
Section: Discussionmentioning
confidence: 99%
“…In previous analyses comparing IDS and ADS on this subset of the corpus, pitch was found to be higher (particularly in stressed vowels) in IDS and there was also a trend for more peripherality in IDS, but no stable differences in vowel duration were seen (Wang et al, 2015). Also, an analysis of the whole corpus has shown greater variability in acoustic characteristics of stressed vowels in IDS than ADS (weak vowels had not been marked or analyzed) (Cristia and Seidl, 2014).…”
Section: Corpus Characteristicsmentioning
confidence: 80%
“…In that study, only one vowel per target word was coded and analyzed. A subset of caregivers was used for the present purposes because their speech had also been coded to investigate whether IDS and ADS differed to similar extents in the weak and strong vowels of bisyllabic and trochaic target word (Wang et al, 2015). This meant that we had access to the temporal location of both strong and weak vowels in some of the target words.…”
Section: Recording and Human Coding Proceduresmentioning
confidence: 99%
“…Lee et al (2014), in an analysis of speech samples of Australian English mothers talking to their infants and to other adults, found that prominence contrasts (as measured by various auditory-model derived metrics) between the vowels of stressed and unstressed syllables were reduced in IDS compared to ADS. In addition, Wang et al (2015) analyzed trochaic words in the conversational speech of American English mothers of 4-and 11-month-old infants; they found no evidence of register differences in the use of durational, F0, or vowel quality cues to lexical stress.…”
Section: The Current Studymentioning
confidence: 99%
“…Following Lee et al (2014) and Wang et al (2015), we measured the duration, intensity, F0, vowel peripherality, spectral tilt, and L max of the vocalic nuclei of all the stressed and unstressed syllables from our stimuli. All coding and analyses were done using Praat software (Boersma and Weenink, 2013).…”
Section: Acoustical Analysesmentioning
confidence: 99%